Chronic Q Fever with No Elevation of Inflammatory Markers: A Case Report - Matteo Boattini; André Almeida; Rita Barata Moura; João Abreu; Ana Sofia Santos; Miguel Toscano Rico (Case Reports in Medicine)
We describe the case of a 55-year-old man with a biological prosthetic aortic valve who suffered from epigastrium and right hypochondrium pain associated with intermittent night sweats. Liver biopsy showed infectious hepatitis pattern without pathognomonic features. Coxiella burnetii serology was suggestive of chronic Q fever, and modified Duke's criteria for endocarditis were also fulfilled. The authors present a brief literature review concerning chronic Q fever, emphasizing absent previous reports of chronic Q fever with hepatitis and endocarditis and no increase in inflammatory markers.